2009
DOI: 10.1007/978-3-642-04568-4_3
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Scorecard for Open Innovation: Measuring the Impact of Industry-University Collaboration

Abstract: Abstract. The Balanced Scorecard (BSC) can be considered as a strategic measurement tool. Since its first publication by Norton and Kaplan in the early 1990's, many companies have applied it to measure four key aspects of their organisations' performance: Financial, Customer, Internal Business Process, Learning and Growth. Although it is widely used in the business arena, this original BSC was not developed to assess the impact of collaborative research projects under an open innovation strategy, where the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
9
0
7
Order By: Relevance
“…CEMEX -Cranfield University research project objectives This study is a collaboration between CEMEX and Cranfield University with the following objectives (Flores et al 2009):…”
Section: Production Planning and Control 555mentioning
confidence: 99%
See 1 more Smart Citation
“…CEMEX -Cranfield University research project objectives This study is a collaboration between CEMEX and Cranfield University with the following objectives (Flores et al 2009):…”
Section: Production Planning and Control 555mentioning
confidence: 99%
“…During such project, a survey was developed to carry out interviews in a sample of 10 companies in UK, where it was confirmed that a collaborative BSC is a very useful tool to measure, track and improve the impact of conducting collaborative projects with universities. This article is an extended version of the one presented at the PRO-VE'09 conference (Flores et al 2009. A balanced scorecard for measuring the impact of industry-university collaboration.…”
mentioning
confidence: 99%
“…São notórias as evidências de que a incorporação de novos predicados ao BSC ao longo do tempo, buscam atender a demanda por adaptabilidade às demandas do ensino superior. Ainda na Figura 2, pode-se inferir que as incorporações identificadas levam de encontro ao atendimento da necessidade de ajustes para a melhoria do modelo quando aplicado às universidades, e, mais especificamente, ao saneamento de algumas deficiências, como por exemplo, as fragilidades quando da utilização do BSC para avaliação do impacto entre R&D relatado por Flores et al (2009) …”
Section: Incorporação De Novas Técnicas Métodos E Tecnologias Ao Bscunclassified
“…Chesbrough [3] defends that for firms to be able to successfully implement the co-innovation business model, they have to be capable of sharing their knowledge, being flexible and being responsive. However, Flores et al [2] defend another set of characteristics as being the most important ones for working in an co-innovation business model. Although there is no unique set of common characteristics accepted by the researchers, it is acknowledged that the set of core-values taken by each firm, determine their behaviour in the collaboration process of creation.…”
Section: Applying Value System Management To Support Co-innovationmentioning
confidence: 99%
“…Co-innovation is a new business paradigm where it is assumed that firms or individual persons can establish a partnership with the aim of jointly developing new ideas and new products [1]. These kinds of partnerships raise new challenges in the scope of trust management and intellectual property management [2,3], since the balance between intellectual property sharing and intellectual property protection is hard to manage. Moreover, if partners have different perceptions of outcomes and different notions of the expected behavior, this might, in some cases, lead to some behaviors that compromise collaboration sustainability.…”
Section: Introductionmentioning
confidence: 99%